Dark spot growth and its acceleration factor in organic light-emitting diodes with single barrier structure. (16th May 2017) - Okada, Takeru; Yoshida, Ayako; Tsuji, Taishi
Abstract: Using organic light-emitting diodes (OLEDs) without encapsulation, dark spot growth and its acceleration factor at high temperature and high humidity were measured and compared with those of edge shrink at the cathode edge. The water permeation model explained the time evolution of dark spots and edge shrink, and the acceleration factor was the same between dark spots and edge shrink. The acceleration factor of edge shrink was proportional to the relative humidity at a constant temperature and showed Arrhenius temperature dependence.